Deciphering pathogenicity and virulence of the first Staphylococcus debuckii isolate from diabetic foot osteomyelitis - Abi Najem, Cynthia N.; Magnan, Chloé; Plumet, Lucile; Ahmad-Mansour, Nour; Pouget, Cassandra; Morsli, Madjid; Pantel, Alix; Kissa, Karima; Sotto, Albert; Lavigne, Jean-Philippe; Molle, Virginie (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThis study identifies Staphylococcus debuckii as a new coagulase-negative staphylococcal species isolated from diabetic foot osteomyelitis (DFOM) and provides an in-depth analysis of its pathogenic and virulence profile, as well as demonstrating its potential to cause infection.MethodsThe S. debuckii NSD001 strain was examined for its planktonic growth, biofilm production, and phagocytosis rates in murine macrophages compared to S. aureus NSA739. Additionally, persistence and replication within human osteoblasts were investigated, while the zebrafish embryo model was employed to assess virulence. Genomic sequencing and bioinformatic analysis were also conducted to identify genes associated with virulent potential.Results and DiscussionS. debuckii NSD001 exhibited robust planktonic growth and significant biofilm production, highlighting its capacity to initiate and maintain an infection, and demonstrated similar rates of phagocytosis as S. aureus NSA739 in murine macrophages, suggesting a mechanism for evading initial host defenses. The strain persisted and replicated within human osteoblasts, indicative of a strategy for intracellular survival and facilitation of chronic osteomyelitis. The zebrafish embryo model revealed a slower, yet fatal, virulence profile for S. debuckii NSD001 compared to the rapid lethality induced by S. aureus NSA739. Genomic sequencing and bioinformatic analysis uncovered various genes corroborating its virulence. S. debuckii NSD001 poses a significant concern in DFOM due to its ability to form biofilms and survive within host cells, presenting challenges for current treatment strategies. This underscores the need for updated clinical protocols and increased awareness among healthcare professionals to effectively manage infections caused by this emerging pathogen.